2021
DOI: 10.1093/ndt/gfab314
|View full text |Cite
|
Sign up to set email alerts
|

Combining phosphate binder therapy with vitamin K2 inhibits vascular calcification in an experimental animal model of kidney failure

Abstract: Background Hyperphosphatemia is strongly associated with cardiovascular disease and mortality. Recently, phosphate binders (PBs), which are used to bind intestinal phosphate have been shown also to bind vitamin K, thereby potentially aggravating vitamin K deficiency. This vitamin K-binding by PBs may offset beneficial effects of phosphate level reduction on reducing vascular calcification (VC). Here we assessed whether combining PBs with vitamin K2 supplementation inhibits VC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 52 publications
(77 reference statements)
0
6
1
1
Order By: Relevance
“…While experimentally the combination of any phosphate binder with vitamin K2 was more potent than either measure alone to retard progression of calcification [31], there are also data indicating that sevelamer in particular may interfere with vitamin K absorption in dialysis patients [26,32]. However, within the limitations of our trial, we found no evidence for any significant effect of sevelamer on the efficacy of our vitamin K1 therapy.…”
Section: Discussioncontrasting
confidence: 53%
“…While experimentally the combination of any phosphate binder with vitamin K2 was more potent than either measure alone to retard progression of calcification [31], there are also data indicating that sevelamer in particular may interfere with vitamin K absorption in dialysis patients [26,32]. However, within the limitations of our trial, we found no evidence for any significant effect of sevelamer on the efficacy of our vitamin K1 therapy.…”
Section: Discussioncontrasting
confidence: 53%
“…Thus, the increased serum Glu-OC in the condition of uremia and hyperparathyroidism, observed in this study, does not necessarily reflect VK deficiency. A good alternative to determine VK status is measurement serum ucMGP, which is a recognized marker of VK status in nephrectomized rats [ 63 ]. In contrast to Glu-OC, ucMGP concentration did not differ between the studied groups in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Известно, что фосфат-связываю щий препарат, севеламера карбонат, обладает плейотропными эффектами на параметры, связанные с сердечно-сосудистым риском: улучшение эндотелиальной и/или сосудистой функции, замедление сосудистой кальцификации, снижение уровня FGF-23, уменьшение количества провоспалительных и окислительных молекул [20,21].…”
Section: Discussionunclassified